2018
DOI: 10.5098/hmt.10.24
|View full text |Cite
|
Sign up to set email alerts
|

Double-Diffusive Natural Convection of Low Prandtl Number Liquids With Soret and Dufour Effects

Abstract: An unsteady numerical model for double-diffusive natural convection of low Prandtl number liquids with Soret and Dufour effects inside the horizontal cavity is developed. The thermosolutal model is solved numerically using the SIMPLE algorithm with QUICK scheme. The flow field, temperature and concentration distributions for different buoyancy ratios, Rayleigh numbers and aspect ratios under different Prandtl numbers are studied systematically. The results reveal that the flow structure develops from conductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Zhou et al (2017) studied which turbulence model was more suitable for simulating the convective heat transfer across a single tube; the results showed that when the Reynolds numbers were low, the DNS gave good results and the LES and RSM were preferred for high Reynolds numbers. Qiu et al (2018) simulated double-diffusive natural convection under different Prandtl numbers in the horizontal cavity and found that the mass transfer intensity increased faster than the heat transfer intensity. Fusegi (1997) simulated flow and heat transfer in a 2D channel with periodic heated cavities and found that heat transfer rates were enhanced with the increase of the Womersley number.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%
“…Zhou et al (2017) studied which turbulence model was more suitable for simulating the convective heat transfer across a single tube; the results showed that when the Reynolds numbers were low, the DNS gave good results and the LES and RSM were preferred for high Reynolds numbers. Qiu et al (2018) simulated double-diffusive natural convection under different Prandtl numbers in the horizontal cavity and found that the mass transfer intensity increased faster than the heat transfer intensity. Fusegi (1997) simulated flow and heat transfer in a 2D channel with periodic heated cavities and found that heat transfer rates were enhanced with the increase of the Womersley number.…”
Section: Frontiers In Heat and Mass Transfermentioning
confidence: 99%